2021
DOI: 10.1210/clinem/dgab382
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Thyroid Disorders and Risk for Type 2 Diabetes in Young Adulthood

Abstract: CONTEXT Thyroid hormones play a key role in systemic metabolism, yet the relationship between thyroid dysfunction and risk for type 2 diabetes is unclear. OBJECTIVE To assess type 2 diabetes risk in adulthood among adolescents with thyroid disorders. DESIGN AND SETTING A nationwide, population-based study of Israeli adolescents who were examined before milita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Therefore, further investigating the effects of thyroid function on diabetes is necessary. A clinical research article by Bardugo et al 3 showed an association of thyroid disorders with the risk of young-onset (YOD) T2D. This study's major finding was that thyroid disorders diagnosed in adolescents were risk factors for early onset T2D 4 in both men and women.…”
Section: E T T E R T O T H E E D I T Omentioning
confidence: 77%
“…Therefore, further investigating the effects of thyroid function on diabetes is necessary. A clinical research article by Bardugo et al 3 showed an association of thyroid disorders with the risk of young-onset (YOD) T2D. This study's major finding was that thyroid disorders diagnosed in adolescents were risk factors for early onset T2D 4 in both men and women.…”
Section: E T T E R T O T H E E D I T Omentioning
confidence: 77%
“…Thyroid diseases and T2D often coexist in the same patients, reinforcing the hypothesis of a reciprocal relationship between these two disorders [9,[98][99][100]. Indeed, THs exert a series of effects on glucose metabolism, as suggested by the action of THs on the pancreas in modulating the development and function of pancreatic β-cells [101,102].…”
Section: Thyroid and Type 2 Diabetesmentioning
confidence: 83%
“…Data regarding immigration history and place of residence were received from the Ministry of Interior [ 26 ]. Residential socioeconomic status was classified into three groups (low/medium/high) based on criteria of the Israeli Bureau of Statistics [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%